POINT VIEW OF DEPORTASION ON INTERNATIONAL LAW - Tony Mirwanto; Asto Yudho Kartiko (Polteknik Imigrasi, 2020)
Immigration is an agency that oversees and acts against foreigners, in addition to that immigration also has a big impact on Indonesia. One of the actions taken by immigration is deportation. Deportation is the attitude of the immigration authorities for foreigners who are suspected or should be suspected of endangering the environment and disturbing public order. Based on the above statement, it can be concluded the formulation of the problem namely how international law views immigration acts, namely deportation. The research method for compiling this journal is the normative-empirical method. Indonesian immigration authorities must urge foreign citizens to comply with the provisions in force in Indonesia so that no party is harmed by the public at large.